Influence of rootstocks on the resistance of cashew plantlets to salt stress - Ferreira-Silva, Sérgio Luiz; Voigt, Eduardo Luiz; Viégas, Ricardo Almeida; Paiva, João Rodrigues de; Silveira, Joaquim Albenísio Gomes (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the influence of cashew (Anacardium occidentale L.) rootstocks on salt resistance in grafted plantlets. The plantlets were obtained by grafting the BRS 226 scion on CAPI 4, CCP 09 and BRS 226 rootstocks, and were exposed to nutrient solution without NaCl (control) or with 200 mM NaCl (salt treatment) in hydroponics under controlled temperature, humidity, and luminosity conditions during 12 days. The experimental design was a completely randomized in factorial arrangement 3x2 (three scion/rootstock combinations, two NaCl concentrations) with four replicates. Na+, Cl-, K+ and organic solute concentrations and toxicity symptoms on leaves were determined. Na+ and Cl- contents, the K+/Na+ ratio and the free amino acid and proline concentrations in leaves were directly related to the visual toxicity symptoms. The rootstocks were classified as sensitive (CAPI 4), intermediate (CCP 09), and resistant (BRS 226) to high salinity. This variation was a consequence of the rootstock influence on Na+ and Cl- partitioning.